2008
DOI: 10.1186/1477-7827-6-31
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the biopotency of follitropin alfa and lutropin alfa combined in one injection: a comparative trial in Sprague-Dawley rats

Abstract: Mixing follitropin alfa RFF and lutropin alfa did not alter the bioactivity of either FSH or LH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…This could be accomplished by combining pure, recombinant preparations of each protein in a fixed and controllable ratio. Alper et al. (2008) reported that combining FSH and LH into one dose and treating rats did not affect either of the proteins bioactivity.…”
Section: Challenges Within the Current Bovine Superovulation Systemmentioning
confidence: 99%
“…This could be accomplished by combining pure, recombinant preparations of each protein in a fixed and controllable ratio. Alper et al. (2008) reported that combining FSH and LH into one dose and treating rats did not affect either of the proteins bioactivity.…”
Section: Challenges Within the Current Bovine Superovulation Systemmentioning
confidence: 99%
“…The authors found no evidence of pharmacokinetic or pharmacodynamic interactions between follitropin alfa and lutropin alfa. More recently, it has been demonstrated that r-hLH and r-hFSH can be mixed together in the same syringe without compromising the bioactivity of the gonadotrophins [ 14 ], and administered successfully to patients [ 15 ]. Purified urinary gonadotrophin products can also be reconstituted and mixed together in a single syringe without affecting the FSH or LH bioactivity [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…8 Our group had established several biological assay methods for the quality control of TCMs, such as purgative activity assays, cardiac activity assays, antiviral activity assays, and antiplatelet aggregation assays. [8][9][10][11][12][13][14][15][16][17][18] Despite the potential advantage of being able to show close association with clinical efficacy, biological assays still have some limitations, such as limited operability, high cost, low precision, and animal ethics issues, when live animals are used in some instances. 2,[19][20][21][22] However, those limitations are usually not limitations for chemical analyses.…”
Section: Introductionmentioning
confidence: 99%